Biomineralization-inspired nanozyme for single-wavelength laser activated photothermal-photodynamic synergistic treatment against hypoxic tumors. Issue 6 (5th February 2020) - Xu, Pengping; Wang, Xueying; Li, Tuanwei; Wu, Huihui; Li, Lingli; Chen, Zhaolin; Zhang, Lei; Guo, Zhen; Chen, Qianwang
Abstract : Bio-inspired multifunctional nanozyme enables synergistic photothermal and photodynamic therapy for hypoxic solid tumors in vivo . Abstract : Hypoxia, one of the features of most solid tumors, can severely impede the efficiency of oxygen-dependent treatments such as chemotherapy, radiotherapy and type-II photodynamic therapy. Herein, a catalase-like nanozyme RuO2 @BSA (RB) was first prepared through a biomineralization strategy, and a high efficiency near-infrared photosensitizer (IR-808-Br2 ) was further loaded into the protein shell to generate the safe and versatile RuO2 @BSA@IR-808-Br2 (RBIR) for the imaging-guided enhanced phototherapy against hypoxic tumors. RB not only acts like a catalase, but also serves as a photothermal agent that speeds up the oxygen supply under near-infrared irradiation (808 nm). The loaded NIR photosensitizer could immediately convert molecular oxygen (O2 ) to cytotoxic singlet oxygen ( 1 O2 ) upon the same laser irradiation. Results indicated that RBIR achieved enhanced therapeutic outcomes with negligible side effects. Features such as a simple synthetic route and imaging-guided and single-wavelength-excited phototherapy make the nanozyme a promising agent for clinical applications.